Hadis-Hadis Tentang Syafaat Dalam Kitab Saḥīḥ Muslim - Nawir Yuslem; Ardiansyah Ardiansyah; Mukhtaruddin Mukhtaruddin; Ismail Fahmi Arrauf Nasution (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Hadiths about Intercession in the Book of Saḥīḥ MuslimThis article discusses the Hadith about syafaat (intercession) in Sahih Muslim using the thematic hadith approach. The term syafaat (intercession) comes from the root word syaf'u or syafā'ah which literally means intercession (help) to convey a request to Allah or mediation, intercession or intermediary between two people. The author traces the hadiths in Sahih Muslim that talk about the topic of intercession, the result is found that in Sahih Muslim this word with its various derivations (isytiqaq) is repeated 38 times spread over 30 hadiths. In terms of structure or form of expression, the terms of intercession that are spread in Sahih Muslim appear at least in five forms of invented words (isytiqaq) each of which implies different meanings. The following article discusses at least seven kinds of expression of syafaat (intercession) with various meanings with various pressures, such as the substance of intercession, the purpose of intercession, the limitations of intercession, the way to obtain intercession, the giver and recipient of intercession, the time of the appearance of intercession, and the conditions for intercession to occur. The elaboration of these topics intends to emphasize the meaning of intercession and the matters related to it..